2016
DOI: 10.1007/978-3-319-31416-7_11
|View full text |Cite
|
Sign up to set email alerts
|

Commitment and Pro-Environmental Behaviors: Favoring Positive Human-Environment Interactions to Improve Quality of Life

Abstract: Environmental psychology focuses on peopleenvironment relations. These relations are often considered in adaptative terms: how can one avoid degradations, limit the overexploitation of natural resources, or cope with some urban annoyances (noise, pollution, etc.)? From a different perspective, Weiss and Girandola (2009, 2010a, b) suggested developing a positive psychology of sustainable development, dealing with social and dispositional factors that enable satisfaction, quality of life and, even more, individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…More precisely, it reviewed commitment-making strategies and the effects of binding communication on the adoption of PEBs such as waste sorting, recycling, non-activist behaviors in the public sphere and energy saving. The study found that commitment, disagreement and binding communication can strengthen the positive characteristics of interactions between humans and the environment and, thereby, improve quality of life 72 . Building on that, it was found that higher levels of commitment to the environment and greater inclusion of nature in the self separately predicted higher levels of PEB.…”
Section: Discussionmentioning
confidence: 89%
“…More precisely, it reviewed commitment-making strategies and the effects of binding communication on the adoption of PEBs such as waste sorting, recycling, non-activist behaviors in the public sphere and energy saving. The study found that commitment, disagreement and binding communication can strengthen the positive characteristics of interactions between humans and the environment and, thereby, improve quality of life 72 . Building on that, it was found that higher levels of commitment to the environment and greater inclusion of nature in the self separately predicted higher levels of PEB.…”
Section: Discussionmentioning
confidence: 89%
“…A significant literature 1 has sought to explain these apparently inconsistent predictions, employing a dynamic moral self-regard model of self-regulation (Monin and Jordan 2009;Zhong, Liljenquist, and Cain 2009). In line with Demarque and Girandola (2016) we propose a framework in which a consumer may obtain a positive amount of moral self-worth through an initial preparatory choice (e.g., walking rather than driving to work); and when making a subsequent concluding decision, the consumer may manifest behavioural consistency (e.g., by going to a conference by a train rather than by plane), as well as inconsistency (e.g., by going to a conference by a plane rather than by train). Research suggests that the decision to license (vs consistency) occurs whenever the individual perceives the initial act as affecting her moral identity (Blanken, van de Ven, and Zeelenberg 2015;Effron and Conway 2015;Mullen and Monin 2016).…”
Section: Introductionmentioning
confidence: 88%
“…Intrinsic factors like QOL (quality of life) and well-being also have been a point of interest, especially in the recent years. There are conceptual and review papers that discussed the antecedents such as QOL, well-being, intrinsic motivation, trust, values, and communication that lead to environmental, green, and sustainable behavior (Carratini et al 2015;Demarque and Girandola 2017;Félonneau and Cause 2017;Kaiser et al 2017;Peattie 2010;Quoquab and Mohammad 2017;Tapia-Fonllem et al 2017;Venhoeven et al 2017).…”
Section: Focus Toward Quality Of Life (Qol)mentioning
confidence: 99%